ChemInform Abstract: Synthesis of Tetraarylpyridines by Chemo‐Selective Suzuki—Miyaura Reactions of 3, 5‐Dibromo‐2, 6‐dichloropyridine. Issue 43 (October 2015) - Reimann, Sebastian; Parpart, Silvio; Ehlers, Peter; Sharif, Muhammad; Spannenberg, Anke; Langer, Peter
Abstract Conditions for the chemoselective preparation of 3, 5‐diaryl‐2, 6‐dichloropyridines which are further transformed to 2, 3, 5, 6‐tetraarylpyridines bearing two different aryl groups are described.